Cultured cell‐derived extracellular matrices to enhance the osteogenic differentiation and angiogenic properties of human mesenchymal stem/stromal cells. (10th July 2019) - Carvalho, Marta S.; Silva, João C.; Cabral, Joaquim M.S.; da Silva, Cláudia L.; Vashishth, Deepak
Abstract: Cell‐derived extracellular matrix (ECM) consists of a complex assembly of fibrillary proteins, matrix macromolecules, and associated growth factors that mimic the composition and organization of native ECM micro‐environment. Therefore, cultured cell‐derived ECM has been used as a scaffold for tissue engineering settings to create a biomimetic micro‐environment, providing physical, chemical, and mechanical cues to cells, and support cell adhesion, proliferation, migration, and differentiation. Here, we present a new strategy to produce different combinations of decellularized cultured cell‐derived ECM (dECM) obtained from different cultured cell types, namely, mesenchymal stem/stromal cells (MSCs) and human umbilical vein endothelial cells (HUVECs), as well as the coculture of MSC:HUVEC and investigate the effects of its various compositions on cell metabolic activity, osteogenic differentiation, and angiogenic properties of human bone marrow (BM)‐derived MSCs, vital features for adult bone tissue regeneration and repair. Our findings demonstrate that dECM presented higher cell metabolic activity compared with tissue culture polystyrene. More importantly, we show that MSC:HUVEC ECM enhanced the osteogenic and angiogenic potential of BM MSCs, as assessed by in vitro assays. Interestingly, MSC:HUVEC (1:3) ECM demonstrated the best angiogenic response of MSCs in the conditions tested. To the best of our knowledge, this is the first study that demonstrates that dECM derived from a coculture of MSC:HUVEC impacts the osteogenic and angiogenic capabilities of BM MSCs, suggesting the potential use of MSC:HUVEC ECM as a therapeutic product to improve clinical outcomes in bone regeneration.